Effects of nitrogen, phosphorus, potassium and magnesium on growth of the oil palm - Corley, R. H. V.; Mok, C. K. (Cambridge University Press, 1972)
Potassium application appeared to increase dry matter production and yield of oil palms, primarily by increasing leaf area, while nitrogen increased both leaf area and net assimilation rate. Responses to phosphorus and magnesium were harder to interpret. Production of vegetative dry matter attained a fairly constant level at the higher rates of fertilizer application, while the ratio of bunch yield to total dry matter production was little affected by fertilizer treatments. The importance of these results for oil palm breeding, and their possible value in diagnosing fertilizer requirements, are briefly discussed